A Comparison of Safety and Efficacy between Silodosin Monotherapy Versus Silodosin with Tadalafil add on Therapy in Patients with Benign Prostatic Hyperplasia - Arafat, Mohammad Ali; Rana, Masud; Akhter, Md Shakil; Hossain, Tohid Md Saiful (Bangladesh Journal of Urology, 2022)
Background: For relieving symptoms of LUTS due to BPH treatment modalities are watchful waiting, medical treatment and surgery. Among medical treatment, options are alpha 1 adrenoreceptor blockers, 5 alpha reductase inhibitors and recently introduced phospodiesterase 5 inhibitors or combination therapy. Objective: To compare the safety and efficacy of silodosin versus silodosin and tadalafil for treating patients with lower urinary tract symptoms secondary to benign prostatic hyperplasia. Materials and Methods: This prospective observational study was conducted in the Department of Urology, BSMMU, Dhaka from April 2020 to March 2021. A total of 66 patients with LUTS due to BPH were selected by purposive sampling on the basis of selection criteria from OPD of Urology, BSMMU. They were randomly divided into two groups: according to odd or even hospital number and label as A group (odd no) and B group (even no). Group-A were provided with silodosin 8.0 mg daily and group-B were provided with silodosin 8.0 mg and tadalafil 5.0 mg daily (B group). Two patients from each group were excluded due to adverse effect and one patients from each group was lost to follow-up. Final analysis was done on sixty patients (30 from each group). The patients were assessed by IPSS, Qmax and PVR. The results were expressed as frequency & percentage (categorical data) and mean ± SD (numerical data). Unpaired t-tests and paired t tests were performed as applicable using SPSS 22.0 and p <0.05 was considered as the level of significance. Results: Out of sixty six patients, sixty patients completed the study. Two patients from group A was suffering from hypotension and headache and two patients from group B was suffering from ejaculatory dysfunction and dizziness, one patient from each group was lost after 1st follow up, so they were excluded from study. Maximum study subjects were within 51 to 70 years of age in both groups. Mean age of the study subjects was 57.13 ± 9.36 years in Group-A and 59.33 ± 7.09 years in Group-B. Mean prostate volume of the study subjects was 37.93 ± 13.19 ml in Group-A and 35.50 ± 10.57 ml in Group-B. IPSS was reduced to 21.90±3.68 after 6 weeks and 18.90 ± 3.79 after 12 weeks from 25.10 ± 3.96 prior to treatment in Group-A. Similarly, in Group-B, IPSS was reduced from 19.67 ± 3.45 after 6 weeks and 16.37 ± 2.03 after 12 weeks from 23.03 ± 4.16 prior to treatment. PVR decreased to 58.00 ± 20.41 after 6 weeks and 42.10 ± 17.40 after 12 weeks from 74.15 ± 26.40 prior to treatment in Group-A. Similarly, PVR in Group-B reduced to 52.70 ± 12.51 after 6 weeks and 33.57 ± 8.97 after 12 weeks from 66.17 ± 15.50 before treatment. After 6 weeks, Qmax increased to 15.67 ± 2.11 and at 12 weeks17.73 ± 2.66 from 13.39 ± 1.83 before treatment in Group-A. Similarly, after 6 weeks, Qmax in Group- B increased to 16.74 ± 1.14 and at 12 weeks18.94±1.31 from 14.17±1.28 before treatment. Conclusion: Improvements in both silodosin (alpha blocker) group and silodosin in combination with tadalafil (PDE 5 inhibitor) group were found to be effective, safe and satisfactory in treating patients with symptomatic BPH. Even though combination group showed better efficacy than silodosin monotherapy group but as per improvement rate it was not statistically significant. Bangladesh J. Urol. 2021; 24(2): 205-213